MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN ROPES (REVIEW, OVERVIEW, PRESENTATION, EXERCISE, SUMMARY) - Yuffa, Tammara; Kurniati, Lenny; Wahyuni, Arie (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
The learning mathematics to students will be easier to master and understand the concept of linear equation material of one variable through the ROPES learning model. This study aims to determine that with the application of ROPES learning model on linear equation material of one variable can improve students’ learning result, students’ activities, and teachers’ performance. The subject of this study is the students of class VII B in the first semester at MTS Matholiul Ulum Banjaragung, Bangsri, Jepara in 2019/2020. Instruments were tests sheet and questionnaires. The type of this research is a classroom action research with two cycles where each cycle there are two meetings. The stages include planning, implementation, observation and reflection. The results showed an increase in student's ability to solve problems about linear equations of one variable. Based on reflection results in cycles 1 and II, it showed: 1) Students’ learning result is increased, in the cycle I the average result was 64.90 and in cycle II reached 73.18. 2) In cycle I of the first meeting was 59.67% categorized ‘enough’. The second was 6601% categorized ‘good’, and in the cycle II reached 81.15% categorized ‘very good’. 3) Increased teacher performance in the first cycle was 60% categorized medium, the second meeting reached 70% categorized high, and in cycle II reached 80% categorized very high.Kata kunci: Mathematical Learning Result, ROPES Learning Model.